21st century skills : learning for life in our times - Trilling, Bernie; Fadel, Charles; Partnership for 21st Century Skills (San Francisco : Jossey-Bass, 2009)
This important resource introduces a framework for 21st Century learning that maps out the skills needed to survive and thrive in a complex and connected world. 21st Century content includes the basic core subjects of reading, writing, and arithmetic-but also emphasizes global awareness, financial/economic literacy, and health issues. The skills fall into three categories: learning and innovations skills; digital literacy skills; and life and career skills. This book is filled with vignettes, international examples, and classroom samples that help illustrate the framework and provide an exciting view of what twenty-first century teaching and learning can achieve.
Book is accompanied by one computer optical discs entitled'1st century skills : learning for life in our times' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references (p. 187-195) and index.
Keywords: Educational planning -- United States; Education -- Aims and objectives -- United States; Educational change -- United States; Life skills -- Study and teaching -- United States